Optimization and Characterization of Lisinopril Loaded Transdermal Patches by Using Factorial Design - Rani, Mukesh; Rohilla, Seema; Sharma, Sangeet; Chadda, Twinkle (Indian Journal of Pharmaceutical Education and Research, 2026)
Background and purpose: This study aimed for systemic and sustained delivery of drug via non-parental route. Materials and Methods: Transdermal patches were prepared by using solvent evaporation method and optimized using 2-factor, 3-level design to investigate the influence of Ethyl Cellulose and HPMC on their tensile strength and drug release. Results: Optimized transdermal patches have shown uniform drug distribution with tensile strength 3.54±0.40 kg/mm2 and in vitro release 94.41±8.7%. The drug content was found to be between 93.84% and 99.62%, indicating a uniform distribution of medication. They were discovered to have a fairly satisfactory moisture content and moisture uptake, which aids in their ability to stay dry and stable. Every formulation underwent an in vitro drug release investigation, and the results showed that the F7 formulation had the highest maximal release of 94.41% in a 24-hr period. The Franz diffusion cell with rat skin in phosphate buffer pH 7.4 was used as the receptor media for ex vivo permeation investigations. Ex vivo skin penetration testing demonstrated that the medication (74.18%) was released in gradually over the course of 24 hr from the optimized patches. Thus, these patches can be used for systemic delivery of drug via non-parental route. Conclusion: The developed transdermal patches may offer sustained and systemic delivery of drugs via non-parental route.
Keywords: Transdermal Patches; Sustained Delivery; Solvent Evaporation Method; Statistical; Experimental Designs; Factorial Design; Lisinopril